Fuelwood consumption patterns and resilience in two rural communities of the Patagonian northwest steppe, Argentina - Cardoso, María Betina (2013)
A comparative ethnobotanical study was carried out in two rural communities in northwest Patagonia. The methodology involved semi structured interviews and free listing, through which richness and use patterns of species used for fuel were registered, as well as socioeconomic factors and alternative fuel sources such as liquefied petroleum gas (LPG) and animal dung. Firewood was found to be a means of subsistence, complemented by the purchase of other firewood resources and the use of alternative fuels. In total 21 species were registered, of which 18 were native species and 3 exotic; 12 fuel species were used by both communities. The species with highest use consensus were Berberis microphylla (michay), Lycium sp. (montenegro) and Senecio subulatus (romerillo) in the Laguna Blanca community, and Salix sp. (sauce) and Senecio subulatus (romerillo) in Comallo. Collection is mainly carried out on foot. Whereas the inhabitants of Laguna Blanca cover large distances in order to collect native woods, in Comallo this is made easier by the use of prunings, obtained closer to dwellings. This is an interesting result since the recycling of biological products to supplement firewood, together with forestation practices, could contribute to the resilience of inhabitants of these arid, hostile environments. We propose that the use of multiple fuel resources could be an indicator of ecological-social resilience processes.